2019
DOI: 10.33640/2405-609x.1018
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of <em>Chasmanthera dependens</em> stem extract mediated silver nanoparticles as Antimicrobial, Antioxidant, Anticoagulant, thrombolytic, and Larvicidal agents

Abstract: Biomedical Applications of Biomedical Applications of Chasmanthera dependens stem extract mediated stem extract mediated silver nanoparticles as Antimicrobial, Antioxidant, Anticoagulant, thrombolytic, silver nanoparticles as Antimicrobial, Antioxidant, Anticoagulant, thrombolytic, and Larvicidal agents and Larvicidal agents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Over the past periods, silver has been proved to be a harmless inorganic antibacterial agent that is non-toxic and well recognized for the assassination of about 650 kinds of diseases producing microbes [15][16][17] . Silver has been labeled as energetic for its capability to exercise potential for a varied variety of biological applications such as anti-fungal agents, anti-bacterial agents, avoiding contagions, healing wounds, and anti-inflammatory even at low concentrations 18,19 . Silver ions are involved in the devising of dental resins, bone adhesive, ion exchange fibers, and medical tools coating 20 .…”
mentioning
confidence: 99%
“…Over the past periods, silver has been proved to be a harmless inorganic antibacterial agent that is non-toxic and well recognized for the assassination of about 650 kinds of diseases producing microbes [15][16][17] . Silver has been labeled as energetic for its capability to exercise potential for a varied variety of biological applications such as anti-fungal agents, anti-bacterial agents, avoiding contagions, healing wounds, and anti-inflammatory even at low concentrations 18,19 . Silver ions are involved in the devising of dental resins, bone adhesive, ion exchange fibers, and medical tools coating 20 .…”
mentioning
confidence: 99%
“…Several authors have reported different colours for AgNPs solution which includes dark brown reported by Aina et al [44] and Lateef et al [45] using Chasmanthera dependens and Petiveria alliacea plant materials, respectively, while reddish brown colouration was reported for corn silk AgNPs [28]. Lateef et al [20] reported the formation of dark brown AgNPs solution using the crude extracellular keratinase of the strain of B. safensis LAU 13, Jeevan et al [46] reported the formation of yellowish-brown AgNPs using cultured supernatant of Pseudomonas aeruginosa, while Oladipo et al [22] reported dark brown AgNPs using cell free-extracts of Enterococcus species.…”
Section: Biosynthesis and Characterization Of Agnpsmentioning
confidence: 97%
“…Thus, the concentration of 5 mM would be ideal for the further optimization of pH factor. For this purpose, the extract and 5 mM silver nitrate solution were adjusted to different pH (7,9,12); with increasing the reaction pH, the absorbance band exhibited a peak at the area of 400 nm (Figure 2(d)). It seems that electrical charges of biomolecules were changed by reaction pH, and possible to influence their capping and stabilizing capacities and subsequently the synthesis and growth rate of NPs (54).…”
Section: Biosynthesis Of Snpsmentioning
confidence: 99%